Austenitic stainless steel degaussing treatment method based on multi-technology cooperation
Through the multi-technical coordinated austenitic stainless steel demagnetization treatment method, including high-temperature solution optimization treatment, nanoscale manipulation demagnetization treatment, pulsed magnetic field reverse demagnetization strengthening treatment, laser demagnetization treatment and ultrasonic and electromagnetic field compound demagnetization treatment, the problem of uneven demagnetization effects and difficulty in reaching extremely low magnetic levels in the prior art is solved, and efficient and uniform demagnetization effects and material performance are achieved.
Patent Information
- Application Number
- CN202411975201.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing austenitic stainless steel demagnetization treatment technology has problems such as high energy consumption, long processing time, uneven demagnetization effect and difficulty in reaching extremely low magnetic levels, especially in high-precision application scenarios, which cannot meet the strict magnetic accuracy requirements.
The austenitic stainless steel demagnetization treatment method is adopted with multiple technologies, including high-temperature solution optimization treatment, nanoscale manipulation demagnetization treatment, pulsed magnetic field reverse demagnetization strengthening treatment, laser demagnetization treatment and ultrasonic and electromagnetic field compound demagnetization treatment. Through the synergy of multiple technologies, a more thorough and uniform demagnetization effect is achieved.
The magnetic properties of 304 austenitic stainless steel are significantly reduced, and the saturated magnetic moment and residual magnetization strength are below 0.1emu/g and below 0.05emu/cm3. The demagnetization effect is far better than that of traditional methods, and has good uniformity. Other properties of the material, such as mechanical properties and corrosion resistance, are also maintained well.
Smart Images

Figure CN119763981A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of austenitic stainless steel manufacturing, and in particular relates to a multi-technique coordinated austenitic stainless steel demagnetization treatment method. Background Art
[0002] In the diversified pattern of modern industry, 304 austenitic stainless steel is widely used in many fields due to its excellent corrosion resistance, good processing and formability and relatively suitable cost. For example, in the chemical industry, it is used in various reaction vessels and piping systems; in the food processing field, it is commonly seen in food processing equipment and storage containers; in medical equipment, it is used in surgical instruments, implant shells, etc.; in the field of architectural decoration, it is used in decorative structures such as curtain walls and railings.
[0003] However, in certain specific application scenarios, the magnetic performance of 304 austenitic stainless steel has become a key factor restricting its further application. Especially in the field of electronic semiconductor manufacturing, ultra-pure fluid control systems require extremely low magnetism to avoid interference with the precise control of the fluid; in ultra-high-precision electronic equipment, magnetism may affect the performance of electronic components and the accuracy of signal transmission; the fluid control system of high-end medical equipment also has strict requirements on magnetism to ensure the high-precision operation of the equipment and the accuracy of the test results.
[0004] The existing 304 austenitic stainless steel demagnetization treatment technologies mainly include traditional methods such as thermal demagnetization and AC demagnetization. Although the principle of thermal demagnetization is simple, that is, heating the material to above the Curie point and then slowly cooling it, it faces many problems in actual operation. On the one hand, the energy consumption is high, and a large amount of energy is required to heat the material to a high temperature state; on the other hand, the processing time is long, and the entire heating, insulation and cooling process takes a long time. More importantly, during the cooling process, since the cooling rate is difficult to accurately control, it is easy to cause changes in the microstructure of the material, such as uneven grain growth, residual stress, etc., which in turn affects other properties of the material, such as mechanical properties and corrosion resistance, and ultimately makes the demagnetization effect unstable, which is difficult to meet the strict requirements of high-precision application scenarios.
[0005] The AC demagnetization method is to place the material in an alternating magnetic field and demagnetize it by gradually reducing the magnetic field strength to zero. However, this method has obvious limitations for 304 austenitic stainless steel parts with complex shapes. Due to the uneven distribution of the alternating magnetic field in complex-shaped parts, the intensity of the magnetic field acting on different parts varies greatly, resulting in uneven demagnetization effects. In some high-precision application scenarios, such as electronic semiconductor manufacturing and high-end medical equipment, this uneven demagnetization effect cannot meet the strict requirements for magnetic accuracy, and it is difficult to reduce the magnetism to the extremely low level required in these fields. Summary of the invention
[0006] In view of this, the present invention aims to propose a multi-technique coordinated demagnetization method for austenitic stainless steel. The use of multiple technologies for coordinated demagnetization can not only completely solve the magnetic problem, but also ensure that other key properties of the material are not affected, thereby meeting the growing demand for high-precision and high-performance applications and improving the competitiveness and applicability of 304 austenitic stainless steel in the high-end market.
[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A multi-technique collaborative austenitic stainless steel demagnetization treatment method, the method comprising the following steps:
[0009] S1. High temperature solution optimization treatment
[0010] The stainless steel material is placed in a heating device to heat up, and then kept warm after reaching the set temperature; after the insulation is completed, the material is immediately water quenched to inhibit the formation of ferrite and martensite and form a single austenite phase to reduce magnetism;
[0011] S2. Nanoscale manipulation and demagnetization
[0012] The use of focused ion beam technology to introduce nano holes or nano stripes on the surface of stainless steel materials can destroy the surface structure of the material at the microscopic level. The nano-processed stainless steel material is then placed in an annealing furnace for annealing. After annealing, the fusion of the nano structure and the matrix is promoted, the internal stress is released, the magnetic properties are optimized, and it is conducive to the synergy with subsequent demagnetization technologies to improve the overall demagnetization effect.
[0013] S3, pulse magnetic field reverse demagnetization strengthening treatment
[0014] Apply a pulsed magnetic field to the treated material. The direction of the pulsed magnetic field is opposite to the direction of the residual magnetic field of the material, and the material must be located at the center of the magnetic field to promote orderly rearrangement of magnetic domains and eliminate residual magnetism.
[0015] S4, laser degaussing
[0016] Design the scanning path according to the shape, size and demagnetization requirements of the component, use the laser to scan the material surface, so that the temperature rises quickly to above the austenite transformation temperature, causing the local magnetic domains on the surface to reorient violently, thus achieving demagnetization;
[0017] S5. Ultrasonic and electromagnetic field composite demagnetization treatment
[0018] Place the treated stainless steel material in a composite demagnetization device with ultrasound and electromagnetic field, select the appropriate ultrasonic transducer and electromagnetic coil layout according to the shape of the component, ensure that the ultrasound and electromagnetic field energy evenly cover the component, and keep the ultrasound and electromagnetic field working together for 30min-50min.
[0019] Further, in S2, the depth of the nanoholes or nanostripes is 30-100 nm; the annealing temperature is 200-300° C., and the annealing time is 1-2 h;
[0020] In S5, the electromagnetic field and the ultrasonic wave propagation direction form a 45° angle, and they work together for 40-50 minutes, causing the internal magnetic domains to rotate and rearrange violently, enhancing the demagnetization effect. Among them, the ultrasonic wave propagation direction is directly facing the component, and the electromagnetic field propagation direction is diagonally facing the component, thus forming a 45° angle; or the ultrasonic wave and magnetic field propagation directions are not directly facing the component to form a 45° angle.
[0021] Furthermore, in S5, the angle error between the electromagnetic field and the ultrasonic wave propagation direction is within ±5°.
[0022] Further, in S1, the temperature is raised to 1050-1200°C at a heating rate of 2-5°C / min and kept at this temperature for 60-240min to fully austenitize the microstructure; the cooling water temperature is 20-30°C and the water flow rate is 5-10m / s.
[0023] Furthermore, in S2, before introducing the nanopores or nanostripes, the material surface needs to be pretreated.
[0024] Furthermore, the pretreatment method is: using ultrasonic cleaning for 20-40 minutes to remove oil and impurities on the surface of the stainless steel to achieve nano-level cleanliness.
[0025] Furthermore, in S3, the magnetic field strength of the pulsed magnetic field is in the range of 650-700 Gs, the frequency is 15-16 Hz, and the pulsed magnetic field is applied continuously for 45-50 minutes.
[0026] Furthermore, in S4, a 1064nm or 532nm high-power pulsed laser is used, with a laser pulse energy of 0.8-2J, a pulse width of 20-50 nanoseconds, and a repetition frequency of 3-10kHz.
[0027] Further, in S5, the frequency of the ultrasonic generator generating ultrasonic waves is 20-50kHz, the power is 100-500W; the electromagnetic field is an alternating electromagnetic field, the intensity is 50-150Gs, and the frequency is 5-10Hz.
[0028] Further, in S5, the composite demagnetization device includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit;
[0029] The ultrasonic generating system includes an ultrasonic generator and an ultrasonic transducer. The ultrasonic generator is connected to the ultrasonic transducer. The ultrasonic generator is responsible for generating an electrical signal of a specific frequency and power. The electrical signal drives the ultrasonic transducer to generate ultrasonic waves. The ultrasonic transducers are distributed according to the shape of the component.
[0030] The electromagnetic field generating system includes a power supply and an electromagnetic coil. The power supply supplies power to the electromagnetic coil to generate an electromagnetic field with a specific frequency and strength. The electromagnetic coil is located inside the ultrasonic transducer. The electromagnetic coil is arranged according to the shape of the component. For example, for a plate component, the coil is reasonably distributed according to its plane shape to ensure uniform coverage of the electromagnetic field. For a rod component, a coil is arranged around the rod to ensure that the magnetic field is evenly distributed around the rod.
[0031] The magnetic sensor array is set close to the surface of the component to monitor the magnetic changes at different positions of the component in real time and transmit the data to the central processing unit. The central processing unit adjusts the frequency of the ultrasonic generator, the power of the ultrasonic wave, the ultrasonic action time, the magnetic field frequency, the magnetic field strength and the magnetic field action time according to the demagnetization effect.
[0032] Specifically, the central processing unit uses intelligent algorithms to analyze data based on preset demagnetization target values (set according to different application scenarios, such as the target magnetic strength of high-end medical equipment housings is usually required to be less than 0.1Gs) and material characteristic parameters (such as the size and shape of the components, the initial magnetic strength after previous processing, etc.). Once it is found that the demagnetization effect of a certain area does not meet the expected standards, the system will automatically adjust the frequency (adjustment step of ±1kHz), power (adjustment step of ±50W), action time (adjustment step of ±5min) of the ultrasonic generator and the frequency (adjustment step of ±2kHz) and intensity (adjustment step of ±100A / m) of the electromagnetic field generation system to ensure that the demagnetization process of the entire component is uniform and can achieve the best effect.
[0033] Furthermore, the distribution of the ultrasonic transducers is arranged according to the shape of the component, including array type, planar matrix type, and surround type.
[0034] The present invention first performs high-temperature solid solution optimization treatment on the stainless steel material, so that the organization is uniformly transformed into austenite, the organization structure is optimized, the material processing performance is improved, the internal organization is more uniform and fine, and good mechanical properties are provided for subsequent mechanical processing, which is the basis for subsequent demagnetization operations. Nanopores or nanostripes are introduced on the surface of the material to destroy the surface structure of the material from a microscopic level, and then annealing is performed to promote the fusion of the nanostructure and the matrix, release internal stress, and optimize magnetic properties. Pulse magnetic field reverse demagnetization strengthening treatment achieves demagnetization by applying a reverse magnetic field to offset the magnetic field of the material itself. Laser demagnetization further eliminates the residual magnetic field from a microscopic perspective by sending a laser to the material. When the laser is irradiated to the magnetic material, the electron spin angular momentum of the material will be rapidly transferred to the atoms of the lattice, causing the magnetism of the material to disappear rapidly.
[0035] Pulse magnetic field reverse demagnetization combined with laser demagnetization can achieve full demagnetization of the two under relatively mild conditions, reducing the internal damage to the material caused by the accumulation of thermal effects. At the same time, pulse demagnetization first makes up for the insufficient elimination efficiency of more staggered magnetic domains that will exist when laser demagnetization is directly used to demagnetize materials after cold deformation. Laser demagnetization can supplement the problem of insufficient precise demagnetization of pulse demagnetization under milder conditions, while reducing the internal stress accumulation caused by pulse demagnetization.
[0036] The pressure waves generated by ultrasound, with their high frequency and high power characteristics, can effectively vibrate the magnetic particles in the magnetic medium, change the direction and distribution of these particles, and then affect the magnetic field in the magnetic medium to achieve the demagnetization effect. Electromagnetic field demagnetization, on the other hand, is to apply an external electromagnetic field to cause the magnetic domains inside the magnetic material to rearrange. The magnetism of magnetic materials originates from the specific arrangement of their internal electron spins and magnetic domains. When an external magnetic field acts on a magnetic material, the magnetic domains will reorganize, resulting in enhanced magnetism of the material. In contrast, the demagnetization process adjusts the arrangement of these magnetic domains to restore them to a relatively disordered state, thereby reducing or eliminating the magnetism of the material.
[0037] Ultrasonic demagnetization and electromagnetic field demagnetization start from the macroscopic physical vibration and microscopic magnetic domain arrangement respectively, and the two complement each other. When used together, electromagnetic field demagnetization can penetrate into the microscopic level of electron spin and magnetic domain arrangement, making up for the limitations of ultrasonic waves in adjusting these subtle structures, thereby significantly improving demagnetization efficiency. At the same time, the synergistic effect of ultrasonic demagnetization and electromagnetic field demagnetization can also ensure a more uniform demagnetization process and improve the overall processing quality.
[0038] Compared with the prior art, the multi-technique coordinated austenitic stainless steel demagnetization treatment method of the present invention has the following advantages:
[0039] 1. Significant demagnetization effect: After the 304 stainless steel sample is treated by the present invention, its saturation magnetic moment is reduced to below 0.1emu / g, and the residual magnetization intensity is reduced to 0.05emu / cm 3 Below, the demagnetization effect is far better than traditional methods.
[0040] 2. Good demagnetization uniformity: It overcomes the problem of uneven demagnetization in complex-shaped components by traditional AC demagnetization method, and multiple technologies work together to achieve uniform and stable demagnetization.
[0041] 3. Stable microstructure: High-temperature solid solution optimization treatment precisely controls the temperature, inhibits the formation of ferrite and martensite, maintains the stability of the austenite structure, and avoids performance degradation caused by microstructural changes.
[0042] 4. Good mechanical properties and corrosion resistance: The tensile strength of the treated material remains between 500-680MPa, the yield strength is between 200-280MPa, the hardness is between 150-190HB, and the corrosion resistance is equivalent to that before treatment, meeting the requirements for high-end equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0044] Figure 1 This is the microstructure morphology of the electronic device housing sample in Example 1;
[0045] Figure 2 This is the microstructure morphology of the precision parts of medical devices in Example 2;
[0046] Figure 3 is the XRD spectrum of the medical device precision component before and after demagnetization in Example 2;
[0047] Figure 4 This is the microstructure morphology of the chemical pipeline connector of Example 3;
[0048] Figure 5 This is the microstructural morphology of Example 4 which lacks nanoscale controlled demagnetization treatment. DETAILED DESCRIPTION
[0049] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0050] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0051] Example 1 Electronic equipment housing sample
[0052] The demagnetization process comprises the following steps:
[0053] S1. High temperature solution optimization treatment
[0054] Select the electronic equipment housing sample made of 304 austenitic stainless steel and place it in a precise temperature control heating device. Heat it to 1100℃ at 3℃ / min. Monitor the temperature during the heating process to ensure the rate is stable. Keep it warm for 120min after reaching 1100℃. After the insulation is completed, immediately water quench and cool it down. The water temperature is 25℃ and the water flow rate is 8m / s.
[0055] S2. Nanoscale manipulation and demagnetization
[0056] Surface pretreatment: Ultrasonic cleaning for 30 minutes to remove surface oil and impurities.
[0057] Nanofabrication: Focused ion beam (FIB) technology was used to introduce 50nm deep holes into the surface.
[0058] Annealing treatment: anneal in 250℃ low temperature annealing furnace for 1.5h.
[0059] S3, pulse magnetic field reverse demagnetization strengthening treatment
[0060] A pulsed magnetic field is applied to the treated material. The direction of the pulsed magnetic field is opposite to the direction of the residual magnetic field of the material. A high-precision positioning device is used to ensure that the material is located at the center of the magnetic field, promoting orderly rearrangement of the magnetic domains and eliminating residual magnetism. The magnetic field intensity is 680Gs, the frequency is 15.5Hz, and it lasts for 48min.
[0061] S4, laser degaussing
[0062] The scanning path is designed according to the shape of the sample. For shells with complex shapes, a combination of partition scanning and overlapping scanning is used. First, the structure is divided into several relatively regular areas according to its structural characteristics, and the scanning path is planned in each area. Adjacent areas are set with 2-5mm overlapping scanning areas to ensure uniform demagnetization effect of the entire component.
[0063] Fix the shell and use a 1064nm high-power pulsed laser with a laser pulse energy of 1.2J, a pulse width of 30 nanoseconds, and a repetition frequency of 5kHz.
[0064] S5. Ultrasonic and electromagnetic field composite demagnetization treatment
[0065] The housing is placed in a composite demagnetization device, which includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit;
[0066] The ultrasonic generating system includes an ultrasonic generator and an ultrasonic transducer. The ultrasonic generator is connected to the ultrasonic transducer. The ultrasonic generator is responsible for generating an electrical signal of a specific frequency and power. The electrical signal drives the ultrasonic transducer to generate ultrasonic waves. The ultrasonic transducers are distributed according to the shape of the component.
[0067] The electromagnetic field generating system includes a power supply and an electromagnetic coil. The power supply supplies power to the electromagnetic coil so that it generates an electromagnetic field with a specific frequency and intensity. The electromagnetic coil is located inside the ultrasonic transducer.
[0068] The magnetic sensor array is set close to the surface of the component to monitor the magnetic changes at different positions of the component in real time and transmit the data to the central processing unit. The central processing unit adjusts the frequency of the ultrasonic generator, the power of the ultrasonic wave, the ultrasonic action time, the magnetic field frequency, the magnetic field strength and the magnetic field action time according to the demagnetization effect.
[0069] For complex-shaped parts such as special-shaped shells, the layout of ultrasonic transducers and electromagnetic coils is designed according to their unique shape characteristics; if the surface of the shell is curved or has concave-convex structures, the ultrasonic transducers and electromagnetic coils are arranged in groups and zones. Divide them into multiple groups, and each group supplies energy to different areas of the shell to ensure that every part of the shell can obtain sufficient ultrasonic and electromagnetic field energy, thereby achieving uniform demagnetization.
[0070] Turn on the 35kHz, 300W ultrasonic generator and simultaneously start the 100Gs, 8Hz alternating electromagnetic field generator, adjust the electromagnetic field to a 45° angle with the ultrasonic propagation direction, and let them act together for 45 minutes.
[0071] In this embodiment, the ultrasonic wave propagates in a direction directly facing the component, and the electromagnetic field propagates in a direction obliquely facing the component, thereby forming an angle of 45°.
[0072] Effect:
[0073] After treatment, the magnetism of the sample was significantly reduced and the demagnetization was uniform, with a saturation magnetic moment of 0.08emu / g and a residual magnetization of 0.03emu / cm 3 , the microstructure is stable, the tensile strength is 650MPa, the yield strength is 250MPa, the hardness is 180HB, the corrosion resistance is good, and it meets the requirements of electronic equipment for the shell. The micromorphology of the treated sample is as follows Figure 1 .
[0074] Example 2 Precision parts for medical devices
[0075] The demagnetization process comprises the following steps:
[0076] S1. High temperature solution optimization treatment
[0077] For the precision parts of medical devices made of 304 austenitic stainless steel, this embodiment takes the joint parts of surgical instruments as an example. In the precise temperature control heating equipment, the temperature is raised to 1150°C at 4°C / min, and the temperature is kept for 180 minutes after reaching the temperature. After the insulation, it is immediately water quenched and cooled. The water temperature is 22°C and the water flow rate is 6m / s.
[0078] S2. Nanoscale manipulation and demagnetization
[0079] Surface pretreatment: Ultrasonic cleaning for 40 minutes to remove surface oil and impurities.
[0080] Nanofabrication: Focused ion beam (FIB) technology is used to introduce 80nm deep nano-stripes on the surface.
[0081] Annealing treatment: anneal in 280℃ low temperature annealing furnace for 1h.
[0082] S3, pulse magnetic field reverse demagnetization strengthening treatment
[0083] A pulsed magnetic field is applied to the treated material. The direction of the pulsed magnetic field is opposite to the direction of the residual magnetic field of the material. A high-precision positioning device is used to ensure that the material is located at the center of the magnetic field, promoting orderly rearrangement of the magnetic domains and eliminating residual magnetism. A pulsed magnetic field with an intensity of 660Gs and a frequency of 15Hz is applied for 46 minutes.
[0084] S4, laser degaussing
[0085] The scanning path is designed according to the shape of the sample. For shells with complex shapes, a combination of partition scanning and overlapping scanning is used. First, the structure is divided into several relatively regular areas according to its structural characteristics, and the scanning path is planned in each area. Adjacent areas are set with 2-5mm overlapping scanning areas to ensure uniform demagnetization effect of the entire component.
[0086] A 532nm high-power pulsed laser was selected with a laser pulse energy of 1.5J, a pulse width of 40ns, and a repetition frequency of 8kHz.
[0087] S5. Ultrasonic and electromagnetic field composite demagnetization treatment
[0088] The shell is placed in a composite demagnetization device, which includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit as in Example 1; similarly, for complex-shaped parts such as special-shaped shells, the ultrasonic transducer and the electromagnetic coil layout are designed according to their unique shape characteristics; if the surface of the shell is curved or has a concave-convex structure, the ultrasonic transducer and the electromagnetic coil are arranged in groups and partitions, and they are divided into multiple groups, each of which supplies energy to different areas of the shell to ensure that each part of the shell can obtain sufficient ultrasonic and electromagnetic field energy, thereby achieving uniform demagnetization.
[0089] Turn on the 40kHz, 400W ultrasonic generator and the 120Gs strength, 6Hz frequency alternating electromagnetic field generator, adjust the electromagnetic field to form a 45° angle with the ultrasonic propagation direction, and act together for 45 minutes. In this embodiment, the propagation directions of the ultrasonic wave and the magnetic field do not form a 45° angle directly to the component.
[0090] Effect: Excellent demagnetization effect and uniform demagnetization, saturation magnetic moment is 0.06emu / g, residual magnetization intensity is 0.02emu / cm 3 The material has stable properties, tensile strength of 680MPa, yield strength of 280MPa, hardness of 190HB, good corrosion resistance, ensuring the high-precision performance requirements of medical devices. The microscopic morphology of the processed samples is as follows: Figure 2 . Figure 3This is the XRD spectrum of the precision parts of medical devices before and after demagnetization, which can provide a lot of key information. From the spectrum, it can be seen that the treated parts mainly show the characteristics of austenite single-phase structure. The position, intensity and shape of the diffraction peaks indicate that its phase composition is pure and unaffected by impurities. This is due to the various demagnetization treatment steps, especially the high-temperature solid solution optimization treatment that inhibits the formation of other phases and ensures the stability of material performance. By comparing the spectrum before and after the introduction of nanostripes and annealing, the subtle changes in the peaks can reflect the fusion of the nanostructure and the matrix and the effect on stress, reflecting the effect of nanoscale manipulation of demagnetization treatment. The comparison of the spectrum before and after treatment can also prove that the multi-technology collaborative demagnetization did not destroy the crystal structure and maintained stability, which is the advantage of this demagnetization method. In mass production, the similarity of the spectrum can ensure batch consistency, ensure reliable product performance, and meet industry standards. Its stability also reflects the rationality and stability of the demagnetization process, providing strong support for optimizing the process and ensuring quality.
[0091] Example 3 Chemical Pipeline Connector
[0092] The demagnetization process comprises the following steps:
[0093] S1. High temperature solution optimization treatment
[0094] Taking 304 austenitic stainless steel chemical pipeline connector as an example, it is placed in a heating device and heated to 1050℃ at 2℃ / min. After the temperature stabilizes, it is kept warm for 240 minutes and then water quenched at 30℃ and a water flow rate of 5m / s.
[0095] S2. Nanoscale manipulation and demagnetization
[0096] Surface pretreatment: ultrasonic cleaning for 20 minutes.
[0097] Nanofabrication: Introducing 30nm deep nanoholes using focused ion beam (FIB).
[0098] Annealing treatment: Place in 200℃ annealing furnace for 2h.
[0099] S3, pulse magnetic field reverse demagnetization strengthening treatment
[0100] A pulsed magnetic field is applied to the treated material. The direction of the pulsed magnetic field is opposite to the direction of the residual magnetic field of the material. A high-precision positioning device is used to ensure that the material is located at the center of the magnetic field, promoting orderly rearrangement of the magnetic domains and eliminating residual magnetism. A pulsed magnetic field with a strength of 650Gs and a frequency of 16Hz is applied for 50min.
[0101] S4, laser degaussing
[0102] The scanning path is designed according to the shape of the sample. For shells with complex shapes, a combination of partition scanning and overlapping scanning is used. First, the structure is divided into several relatively regular areas according to its structural characteristics, and the scanning path is planned in each area. Adjacent areas are set with 2-5mm overlapping scanning areas to ensure uniform demagnetization effect of the entire component.
[0103] A 1064nm high-power pulsed laser was used with a laser pulse energy of 0.8J, a pulse width of 20 nanoseconds, and a repetition frequency of 3kHz.
[0104] S5. Ultrasonic and electromagnetic field composite demagnetization treatment
[0105] The shell is placed in a composite demagnetization device, which includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit as in Example 1; similarly, for complex-shaped parts such as special-shaped shells, the ultrasonic transducer and the electromagnetic coil layout are designed according to their unique shape characteristics; if the surface of the shell is curved or has a concave-convex structure, the ultrasonic transducer and the electromagnetic coil are arranged in groups and partitions, and they are divided into multiple groups, each of which supplies energy to different areas of the shell to ensure that each part of the shell can obtain sufficient ultrasonic and electromagnetic field energy, thereby achieving uniform demagnetization.
[0106] Turn on the 20kHz, 100W ultrasonic generator and the 50Gs strength, 10Hz frequency alternating electromagnetic field generator, adjust the electromagnetic field to form a 45° angle with the ultrasonic propagation direction, and act together for 45 minutes. In this embodiment, the ultrasonic propagation direction is directly facing the component, and the electromagnetic field propagation direction is oblique to the component, thus forming a 45° angle.
[0107] Effect: Saturation magnetic moment is 0.07emu / g, residual magnetization is 0.03emu / cm 3 , tensile strength 620MPa, yield strength 220MPa, hardness 160HB, good corrosion resistance, various performance indicators meet the high-precision application requirements of pipeline connectors in the chemical industry, the microscopic morphology of the processed samples is as follows Figure 4 .
[0108] Comparative Example 1 Conventional thermal demagnetization method, compared with Example 1
[0109] A 304 austenitic stainless steel sample of the same specification as in the embodiment was taken, placed in a conventional heating furnace and heated to above the Curie point (about 850° C.), and then naturally cooled in air.
[0110] The test found that the saturation magnetic moment is 2emu / g and the residual magnetization intensity is 1.5emu / cm 3, the grain growth is uneven, residual stress appears, the tensile strength drops to 450MPa, the yield strength drops to 180MPa, the hardness drops to 130HB, the corrosion resistance is affected, and the demagnetization effect is poor.
[0111] Comparative Example 2 Conventional AC demagnetization method, compared with Example 2
[0112] The 304 austenitic stainless steel sample was placed in an alternating magnetic field generating device, and the magnetic field intensity was gradually reduced from the initial value to zero.
[0113] Tests show that the demagnetization effect is uneven for samples with complex shapes, with a saturation magnetic moment of 1.8emu / g and a residual magnetization of 1.2emu / cm 3 , the microstructure changes locally, affecting the overall performance, tensile strength 550MPa, yield strength 200MPa, hardness 140HB, corrosion resistance slightly decreased.
[0114] Comparative Example 3 lacks high temperature solution optimization treatment. Compared with Example 3
[0115] Starting directly from the nanoscale controlled demagnetization treatment, the stainless steel sample was ultrasonically cleaned for 20 minutes, and a 30nm deep nanopore was introduced using the focused ion beam (FIB) technology, and then placed in a 200°C annealing furnace for 2 hours. Then, a pulsed magnetic field with a strength of 650Gs and a frequency of 16Hz was applied for 50 minutes; a laser demagnetization treatment was performed using a 1064nm high-power pulsed laser (parameters are the same as in Example 3); and finally, an ultrasonic and electromagnetic field composite demagnetization treatment was performed (parameters are the same as in Example 3).
[0116] The test found that the saturation magnetic moment is 1.2emu / g and the residual magnetization intensity is 0.8emu / cm 3 , many microstructural defects, tensile strength 480MPa, yield strength 190MPa, hardness 150HB, and decreased corrosion resistance. This shows that not undergoing high-temperature solid solution optimization treatment will not only affect the demagnetization effect, but also the mechanical properties and corrosion resistance of the material. To achieve an excellent demagnetization effect, the steps of the present invention are indispensable.
[0117] Comparative Example 4 lacks nanoscale manipulation demagnetization treatment, compared with Example 2
[0118] After the stainless steel sample was subjected to high temperature solid solution optimization treatment (parameters were the same as those in Example 2), it was directly subjected to pulse magnetic field reverse demagnetization strengthening treatment (parameters were the same as those in Example 2). Subsequently, a 532 nm high power pulse laser (parameters were the same as those in Example 2) was used for laser demagnetization treatment and ultrasonic and electromagnetic field composite demagnetization treatment (parameters were the same as those in Example 2).
[0119] The results show that the saturation magnetic moment is 0.8emu / g and the residual magnetization is 0.5emu / cm3 The material has large internal stress, tensile strength of 580MPa, yield strength of 230MPa, and hardness of 170HB, which has a certain impact on the mechanical properties. This shows that the lack of nanoscale controlled demagnetization treatment will not only affect the demagnetization effect, but also affect the mechanical properties and corrosion resistance of the material. To achieve excellent demagnetization effect, the steps of the present invention are indispensable.
[0120] Figure 5 The present invention shows the microstructure morphology of the comparative example lacking nanoscale manipulation demagnetization treatment, which is significantly different from the embodiment. In terms of grain size, the grains in the comparative example may lack effective regulation due to the lack of nanoscale treatment, resulting in significant growth of some grains and uneven overall size distribution, while the grain size of the embodiment is uniform and relatively small, which is due to the inhibitory effect of nano-treatment on grain growth. In terms of phase composition, the stability of the comparative example is poor, and there may be signs of weak abnormal phases, while the embodiment can maintain good phase stability. In terms of microstructural integrity, the grain boundaries of the comparative example are discontinuous, fuzzy or distorted, reflecting that the internal stress is not effectively released, while the grain boundaries of the embodiment are clear, continuous and smooth, and the atoms are arranged in an orderly manner. In terms of magnetic domain structure, the comparative example lacks nano-treatment, and the magnetic domain distribution is chaotic and uneven, and the increase in defects leads to stress concentration, which affects the demagnetization effect. The embodiment is more uniform and orderly, which is conducive to demagnetization. In terms of microscopic characteristics related to mechanical properties, the slip band distribution of the comparative example is disorderly and the local deformation is serious, indicating that its ability to resist external forces is poor, while the slip bands of the embodiment are uniform and orderly, and the plastic deformation ability is good. In summary, these differences fully highlight the key significance of nanoscale manipulated demagnetization processing in optimizing material properties and improving demagnetization effects.
[0121] Comparative Example 5 lacks the pulse magnetic field reverse demagnetization strengthening treatment, compared with Example 1
[0122] After completing the high temperature solution optimization treatment (parameters are the same as those in Example 1) and the nanoscale manipulation demagnetization treatment (parameters are the same as those in Example 1), a 1064nm high power pulsed laser (parameters are the same as those in Example 1) is directly used for laser demagnetization treatment. Then, an ultrasonic and electromagnetic field composite demagnetization treatment (parameters are the same as those in Example 1) is performed.
[0123] After testing, the saturation magnetic moment is 0.9emu / g and the residual magnetization is 0.6emu / cm 3 , the microstructure is unstable, the tensile strength is 560MPa, the yield strength is 210MPa, and the hardness is 165HB, which affects the overall performance of the material. This shows that the lack of pulse magnetic field reverse demagnetization strengthening treatment will not only affect the demagnetization effect, but also affect the mechanical properties and corrosion resistance of the material. To achieve excellent demagnetization effect, the steps of the present invention are indispensable.
[0124] Comparative Example 6: Different hole sizes produced by nanoscale manipulation and demagnetization
[0125] A- Large void size: The difference from Example 1 is that in the nanoscale manipulation demagnetization treatment step, the depth of the nanopores introduced on the surface of the stainless steel material using the focused ion beam (FIB) technology is 150 nm, and the other treatment steps include high-temperature solid solution optimization treatment (heating rate, holding time, cooling water temperature and flow rate, etc.), subsequent pulsed magnetic field reverse demagnetization strengthening treatment (magnetic field intensity, frequency, duration), laser demagnetization treatment (laser wavelength, pulse energy, pulse width, repetition frequency) and ultrasonic and electromagnetic field composite demagnetization treatment (ultrasonic generator frequency, power, electromagnetic field intensity, frequency, propagation direction angle, etc.) are the same as Example 1.
[0126] B- Small hole size: The only difference between this comparative example and Example 1 is that during the nanoscale manipulation demagnetization treatment, the depth of the nanopores manufactured using the focused ion beam (FIB) technology is 10nm, and the other steps such as high-temperature solid solution optimization treatment, pulsed magnetic field reverse demagnetization strengthening treatment, laser demagnetization treatment, ultrasonic and electromagnetic field composite demagnetization treatment and corresponding parameters remain unchanged.
[0127] Effect:
[0128] A- Large void size: The magnetism of the treated sample is reduced, the saturation magnetic moment reaches 0.1emu / g, and the residual magnetization intensity is 0.08emu / cm 3 However, the demagnetization uniformity is poor, and relatively high magnetic areas appear locally. The material has a tensile strength of 320MPa, a yield strength of 160MPa, and a hardness of 155HB.
[0129] B- Small void size: The sample saturation magnetic moment is 0.6emu / g, and the residual magnetization is 0.3emu / cm 3 The demagnetization effect is uneven, and there are local areas with higher magnetism. The tensile strength of the material is 600MPa, the yield strength is 200MPa, and the hardness is 195HB.
[0130] The impact of large void size: The larger void depth (150nm) changes the magnetic domain structure on the surface of the material to a certain extent, reducing the magnetism. However, such large-sized voids seriously damage the overall structural integrity of the material. A large amount of material is removed to form large voids, which leads to a high concentration of stress inside the material, greatly weakening the mechanical properties of the material, which is manifested in a significant decrease in tensile strength and yield strength. At the same time, the presence of large voids makes the distribution of the magnetic field in the material uneven. During the demagnetization process, the magnetic field is more likely to gather or distort around the void, resulting in inconsistent magnetic domain rearrangement effects in local areas, resulting in relatively high local magnetism.
[0131] The influence of small hole size: Small hole depth (10nm) has relatively limited changes to the magnetic domain structure and cannot provide enough sites to promote the effective rearrangement of magnetic domains, so the demagnetization effect is not as good as that of holes of appropriate size. Although the impact on mechanical properties is relatively small, the overall demagnetization is insufficient and the residual magnetism is large because the optimization effect of nanoscale manipulation demagnetization on the magnetic domain structure cannot be fully utilized, which is manifested as high saturation magnetic moment and residual magnetization, and uneven demagnetization.
[0132] Comparative Example 7: Different annealing conditions for nanoscale manipulation demagnetization
[0133] A: The difference from Example 1 is that in the annealing step after the nanoscale manipulated demagnetization treatment, the stainless steel sample is placed in a 150°C low-temperature annealing furnace for 0.8 h, while other treatment steps such as high-temperature solid solution optimization treatment (heating, insulation, cooling parameters), introduction of nanopores or stripes and surface pretreatment in the nanoscale manipulated demagnetization treatment, pulsed magnetic field reverse demagnetization strengthening treatment (magnetic field parameters), laser demagnetization treatment (laser parameters), and ultrasonic and electromagnetic field composite demagnetization treatment (ultrasonic and electromagnetic field parameters) are the same as in Example 1.
[0134] B: The difference between this comparative example and Example 1 is only the annealing process. The sample is placed in a low-temperature annealing furnace at 350°C for 3 hours, and other processing steps (including high-temperature solid solution optimization treatment, related operations of nanoscale manipulation demagnetization treatment, pulsed magnetic field reverse demagnetization strengthening treatment, laser demagnetization treatment, ultrasonic and electromagnetic field composite demagnetization treatment) and parameters remain unchanged.
[0135] Effect:
[0136] A: After treatment, the saturation magnetic moment of the sample is 1.1emu / g and the residual magnetization is 0.7emu / cm 3 , tensile strength 530MPa, yield strength 210MPa, hardness 190HB.
[0137] B: The sample saturation magnetic moment is 0.9emu / g and the residual magnetization is 0.5emu / cm 3 , tensile strength 480MPa, yield strength 175MPa, hardness 150HB.
[0138] Annealing temperature is low and time is short (case A): The lower annealing temperature (150°C) and shorter annealing time (0.8h) are not enough to fully fuse the nanostructure with the matrix, and the internal stress cannot be effectively released. The incompletely fused nanostructure will interfere with the normal arrangement of the magnetic domains, resulting in higher magnetism, manifested as larger saturation magnetic moment and residual magnetization. In terms of mechanical properties, due to the existence of internal stress, the tensile strength and yield strength of the material are not optimal. Although the hardness is relatively high, this may be due to the hardening of the material caused by internal stress, rather than the optimization of the material's own performance.
[0139] High annealing temperature and long time (case B): Too high annealing temperature (350℃) and too long annealing time (3h) will cause the grain growth of the material. During the grain growth process, the grain boundary area decreases, and the pinning effect of the grain boundary on the magnetic domain is weakened, making the magnetic domain more susceptible to external influences and changes, which is not conducive to the stable demagnetization effect. The saturation magnetic moment and residual magnetization still have a certain value. At the same time, grain growth reduces the strength and hardness of the material, because dislocations in large grains are easier to move and the deformation resistance of the material is reduced, so the tensile strength and yield strength decrease, and the hardness also decreases.
[0140] Comparative Example 8: Electromagnetic field and ultrasonic wave propagation directions are different
[0141] A-The propagation direction is 0°: The difference from Example 1 is that in the ultrasonic and electromagnetic field composite demagnetization treatment, the electromagnetic field and ultrasonic propagation directions are adjusted to 0°, that is, both are facing the stainless steel part, and other processing steps such as high-temperature solid solution optimization treatment (heating rate, holding time, cooling conditions), nanoscale manipulation demagnetization treatment (introduction of nanopores or stripes, annealing, etc.), pulsed magnetic field reverse demagnetization strengthening treatment (magnetic field strength, frequency, duration), laser demagnetization treatment (laser parameters) and ultrasonic generator frequency, power, electromagnetic field strength, frequency and other parameters in the ultrasonic and electromagnetic field composite demagnetization treatment are the same as those in Example 1.
[0142] B-The propagation direction is 20°: The difference between this comparative example and Example 1 is that during the ultrasonic and electromagnetic field composite demagnetization treatment, the propagation directions of the electromagnetic field and the ultrasonic wave are set to 20°, wherein the ultrasonic wave propagation direction is directly facing the component, and the electromagnetic field propagation direction forms an angle of 20° obliquely to the component, and the other treatment steps (including high-temperature solid solution optimization treatment, nanoscale manipulation demagnetization treatment, pulsed magnetic field reverse demagnetization strengthening treatment, laser demagnetization treatment) and corresponding parameters remain unchanged.
[0143] C-propagation direction is 75°: In the comparative example, in the ultrasonic and electromagnetic field composite demagnetization treatment, the electromagnetic field and the ultrasonic propagation direction are made to form an angle of 75° (the ultrasonic wave is facing the component directly, and the electromagnetic field is facing the component diagonally). Other treatment processes such as high-temperature solid solution optimization treatment, nanoscale manipulation demagnetization treatment, pulsed magnetic field reverse demagnetization and strengthening treatment, and laser demagnetization treatment are all consistent with Example 1, and other parameters in the ultrasonic and electromagnetic field composite demagnetization treatment (ultrasonic wave generator frequency, power, electromagnetic field strength, frequency, etc.) also remain unchanged.
[0144] Effect:
[0145] A-propagation direction is 0°: after treatment, the sample saturation magnetic moment is 0.1emu / g, and the residual magnetization is 0.07emu / cm 3 , tensile strength 630MPa, yield strength 245MPa, hardness 180HB.
[0146] B-propagation direction is 20°: the sample saturation magnetic moment is 0.3emu / g, and the residual magnetization intensity is 0.12emu / cm 3 , tensile strength 625MPa, yield strength 220MPa, hardness 175HB.
[0147] C-propagation direction is 75°: after treatment, the saturation magnetic moment is 0.4emu / g and the residual magnetization is 0.26emu / cm 3 , tensile strength 618MPa, yield strength 226MPa, hardness 180HB.
[0148] The electromagnetic field and ultrasound affect the magnetic domains from a microscopic and macroscopic perspective respectively during the demagnetization process. In Example 1, when the electromagnetic field is at a 45° angle to the direction of ultrasound propagation, the synergistic effect of the two is optimal. This is because at this angle, the microscopic rearrangement of the magnetic domains by the electromagnetic field and the macroscopic vibration of the magnetic particles by ultrasound can cooperate with each other to disrupt the orderliness of the magnetic domains to the greatest extent, so that the magnetic domains can be effectively adjusted at different scales, thereby achieving a better demagnetization effect.
[0149] When the propagation direction is 0°, a certain demagnetization effect can be achieved (saturation magnetic moment is 0.1emu / g, residual magnetization intensity is 0.07emu / cm 3 ), but because the electromagnetic field and ultrasonic wave act in the same direction, they may over-act in some areas and under-act in other areas, resulting in uneven demagnetization. At the same time, in this case, the synergistic advantages of the two at different scales may not be fully utilized, making the demagnetization effect slightly inferior to the 45° angle.
[0150] When the propagation direction is 20° or 75°, it deviates from the optimal synergistic angle, and the synergistic effect of the electromagnetic field and ultrasound is weakened. At 20°, the effects of the two cannot complement each other well, resulting in insufficient adjustment of the magnetic domains, a decrease in the demagnetization effect, and an increase in the saturation magnetic moment and residual magnetization. At 75°, due to the large angle deviation, the possibility of mutual interference between the two effects increases, making the rearrangement of the magnetic domains more difficult, and the demagnetization effect is further reduced, which is manifested as a higher saturation magnetic moment and residual magnetization. Although the change in mechanical properties is relatively small, the overall demagnetization effect is not ideal.
[0151] Through the detailed study of the above comparative examples, we can have a deeper understanding of the important influence of the key parameters and sequence in each processing step on the demagnetization effect and material properties of austenitic stainless steel, and provide a strong basis for further optimizing the demagnetization treatment process. In practical applications, the operation should be strictly carried out in accordance with the optimal process parameters and sequence to obtain the ideal demagnetization effect and material properties.
[0152] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A multi-technique collaborative austenitic stainless steel demagnetization treatment method, characterized in that: The method comprises the following steps: S1. High temperature solution optimization treatment The stainless steel material is placed in a heating device to heat up, and then kept warm after reaching the set temperature; after the insulation is completed, the material is immediately water quenched and cooled; S2. Nanoscale manipulation and demagnetization Use focused ion beam technology to introduce nano holes or nano stripes on the surface of stainless steel materials, and then put the nano-processed stainless steel materials into an annealing furnace for annealing; S3, pulse magnetic field reverse demagnetization strengthening treatment Apply a pulsed magnetic field to the treated material. The direction of the pulsed magnetic field is opposite to the direction of the residual magnetic field of the material, and the material must be located at the center of the magnetic field. S4, laser degaussing Design the scanning path according to the shape, size and demagnetization requirements of the parts, use the laser to scan the material surface, and quickly raise the temperature above the austenite transformation temperature; S5. Ultrasonic and electromagnetic field composite demagnetization treatment Place the treated stainless steel material in a composite demagnetization device with ultrasound and electromagnetic field, select the appropriate ultrasonic transducer and electromagnetic coil layout according to the shape of the component, ensure that the ultrasound and electromagnetic field energy evenly cover the component, and keep the ultrasound and electromagnetic field working together for 30min-50min.
2. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 1 is characterized in that: In S2, the depth of the nanoholes or nanostripes is 30-100 nm; the annealing temperature is 200-300°C, and the annealing time is 1-2 h; In S5, the electromagnetic field forms an angle of 45° with the direction of ultrasonic wave propagation and acts together for 40-50 minutes.
3. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 2 is characterized in that: In S5, the angle error between the electromagnetic field and the ultrasonic wave propagation direction is within ±5°.
4. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 1, characterized in that: In S1, the temperature is raised to 1050-1200°C at a heating rate of 2-5°C / min and kept at this temperature for 60-240min; the cooling water temperature is 20-30°C and the water flow rate is 5-10m / s.
5. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 1, characterized in that: In S2, the material surface needs to be pretreated before the nanopores or nanostripes are introduced.
6. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 5 is characterized in that: The pretreatment method is: use ultrasonic cleaning for 20-40 minutes to remove oil and impurities on the surface of stainless steel to achieve nano-level cleanliness.
7. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 1, characterized in that: In S3, the magnetic field strength of the pulsed magnetic field is in the range of 650-700 Gs, the frequency is 15-16 Hz, and the pulsed magnetic field is applied continuously for 45-50 minutes.
8. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 1, characterized in that: In S4, a 1064nm or 532nm high-power pulsed laser is used, with a laser pulse energy of 0.8-2J, a pulse width of 20-50 nanoseconds, and a repetition frequency of 3-10kHz.
9. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 1, characterized in that: In S5, the frequency of the ultrasonic generator for generating ultrasonic waves is 20-50kHz, the power is 100-500W; the electromagnetic field is an alternating electromagnetic field, the intensity is 50-150Gs, and the frequency is 5-10Hz.
10. The multi-technique coordinated austenitic stainless steel demagnetization treatment method according to claim 1, characterized in that: In S5, the composite demagnetization device includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit; The ultrasonic generating system includes an ultrasonic generator and an ultrasonic transducer, the ultrasonic generator is connected to the ultrasonic transducer, and the ultrasonic transducers are distributed according to the shape of the component; The electromagnetic field generating system includes a power supply and an electromagnetic coil, and the electromagnetic coil is located inside the ultrasonic transducer; The magnetic sensor array is set close to the surface of the component to monitor the magnetic changes at different positions of the component in real time and transmit the data to the central processing unit. The central processing unit adjusts the frequency of the ultrasonic generator, the power of the ultrasonic wave, the ultrasonic action time, the magnetic field frequency, the magnetic field strength and the magnetic field action time according to the demagnetization effect.